Vine and Fruit Responses to Supplementary Irrigation and Canopy Management - Mccarthy, M. G.; Cirami, R. M.; Mccloud, P. (South African Journal of Enology and Viticulture, 2017)
Drip irrigation at 0.0, 0.2 or 0.4 of weekly Class A Pan evaporation was applied to grapevines cv. Shiraz in the Barossa Valley of South Australia. Irrigation resulted in a significant increase in yield and vegetative growth but also significantly changed wine composition and wine spectral measures. Canopy management by shoot positioning and treatment with ethephon, both designed to increase fruit exposure to sunlight, resulted in significant but small changes in wine quality measures. The implications of these treatments for the improvement of wine quality from irrigated vines are discussed.